Risk for multidrug-resistant tuberculosis in patients treated with anti-tumor necrosis factor agents - Park, Jinkyeong; Hong, Yoonki; Hong, Ji Young (Frontiers in Medicine, 2023)
Background There are few studies on medical conditions associated with the development of drug-resistant TB. Objective We investigated the risk factors for the occurrence of multidrug-resistant (MDR) tuberculosis (TB) in patients with pulmonary TB. Materials and methods Based on claims data from the Health Insurance Review and Assessment service in South Korea, we retrospectively investigated patients aged 18 years or older with active pulmonary TB who were treated with anti-TB therapy between January 1, 2008, and February 28, 2021. Results Among 248,176 patients with pulmonary TB who underwent anti-TB therapy, 2.0% were identified as having MDR-TB. MDR-TB showed male predominance compared to patients without MDR-TB, and patients with MDR-TB were younger. The risk for MDR-TB in patients treated with anti-TB therapy was 3.26 times higher in patients who received anti-tumor necrosis factor (TNF) agents before prescription of anti-TB medications than in those who had never been exposed to anti-TNF agents after adjusting for other TB risk factors (age, sex, inhaled corticosteroid, diabetes mellitus, liver disease, pneumoconiosis, and organ or blood recipients). The risk for MDR-TB was also increased in males and younger patients. Conclusion Treatment with an anti-TNF agent could be a driver of MDR-TB in patients with pulmonary TB.